Review papersDiagnosis, clinical assessment of HIV infection in a pregnant woman and legal aspects of HIV infection - Żaba, Czesław; Osiński, Maciej (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
HIV infection is diagnosed using serological tests (detection of HIV1/2-specific antibodies) and tests based on molecular biology techniques (detection of viral nucleic acids: HIV RNA, HIV DNA). Currently, infection with HIV mediated by blood-derived preparations is practically impossible. HIV-specific antibodies pass through placenta to foetal blood, where they may persist till 18 th month of life and, therefore, serological tests in children below this age may be falsely positive, which makes establishing a correct diagnosis more difficult. In Poland, only 10% of pregnant women undergo tests aimed to detect infection with HIV while in some Western countries such tests are performed in as many as 98% of pregnant women. During pregnancy in a HIV(+) woman, HIV blood load and number of Th CD4+ lymphocytes should be monitored. In Poland, compulsory tests for presence of HIV infection are performed in persons suspected of HIV infection/AIDS; newborns and infants, pregnant women, carriers and individuals in contact with the infected material.